DESIGN OF ACADEMIC INFORMATION SYSTEM BASED ON BOT TELEGRAM IN SMART CAMPUS CONCEPT - Ahmadi Ahmadi; Dedi Setiawan; Suprayitno Suprayitno; Priyadi Hartoko (JOURNAL ASRO, 2020)
The goal for many education institutions is the existence of the Smart Campus concept. Smart Campus is the concept of a smart campus to provide maximum service to the entire academic community by monitoring and managing existing resources effectively and efficiently. Smart Campus can also provide appropriate information to students or campus institutions in every activity, or even in unexpected events. In this research, it is proposed to maximize the academic information system which is integrated with the Telegram messenger application. This Telegram application can be obtained for free, lightweight and multiplatform by having a fairly complete and more developed Bot API. Students get real time notifications and can chat / communicate with the Telegram Bot which is designed to provide all the information on STTAL. The admin can upload lecture material into the Telegram Bot then students can download it from the Telegram Bot. There are 11 commands designed in this study as a prototype. This research was tested by trying all the commands provided. This Bot Telegram application is very helpful for study program staff and lecturers to convey information to students especially using this application is quite easy. Keywords: Smart Campus, Bot Telegram, and Information Media